Shocks and Business Cycles - Frankel, David M.; Burdzy, Krzysztof (My University, 2005)
A popular theory of business cycles is that they are driven by animal spirits: shifts in expectations brought on by sunspots. A prominent example is Howitt and McAfee (AER, 1992). We show that this model has a unique equilibrium if there are payoff shocks of any size. This equilibrium still has the desirable property that recessions and expansions can occur without any large exogenous shocks. We give an algorithm for computing the equilibrium and study its comparative statics properties. This work generalizes Burdzy, Frankel, and Pauzner (2000) to the case of endogenous frictions and seasonal and mean-reverting shocks.